The Effect of Liquidity, Leverage, and Profitability on the Return of Shares of Manufacturing Companies in the Basic Industrial and Chemical Sub-Sectors Listed on the IDX - Allifah Azhara Sumantri; Cahyo Pramono; Arif Permana Siddik; Asminar Br Siagian; Ahmad Fauzi Pane (Universitas Kristen Indonesia Toraja, 2022)
This research was conducted to determine the influence of the current ratio, debt to equity ratio, and return on assets on stock returns in manufacturing companies in the basic and chemical industry sector listed on the Indonesia Stock Exchange. Data was taken from www.idx.co.id, covering the years 2014 to 2019, and the research was conducted in 2021. The population of this study consisted of 61 companies, with a sample of 39 companies. The research utilized quantitative data processed using the Eviews 9 application with a panel regression method. The test results concluded that only the return on assets variable partially has a significant impact on stock returns, while the current ratio and debt-to-equity ratio variables partially do not have a significant impact on stock returns. Simultaneously, the current ratio, debt to-equity ratio, and return on assets variables also do not significantly affect the stock returns of manufacturing companies in the basic and chemical industry sector. The contribution of the current ratio, debt-to-equity ratio, and return on assets variables to stock returns is only 1.20%, and the correlation level of these variables with stock returns is very weak.